Biochar-Terracotta Conductive Composites: New Design for Bioelectrochemical Systems - Cristiani, Pierangela; Goglio, Andrea; Marzorati, Stefania; Fest-Santini, Stephanie; Schievano, Andrea (Frontiers in Energy Research, 2020)
Research in the field of bioelectrochemical systems is addressing the need of improving components and reducing their costs in the perspective of their large-scale application. In this view, innovative solid separators of electrodes, made of biochar and terracotta, are investigated. Biochar-based composites are produced from giant cane (Arundo Donax L.). Two different types of composite are experimented: i) composite A, produced by pyrolysis of crushed chipping of A.donax L. mixed clay; ii) composite B, produced by pyrolysis of already pyrolyzed giant cane (biochar) mixed with clay. Electrical resistivity, electrical capacity, porosity, water retention, and water leaching of the two composites types (A and B) with 1, 5, 10, 15, 20 and 30 mass percentages of carbon (w/w) are characterized and compared. Less than 1 kΩcm of electrical resistance is obtained for composite A with a carbon content greater than 10 %, while physical and electrical performances of composite B does not significantly change. SEM micrographs and 3D microcomputed tomography of different composite materials are provided, demonstrating a different matrix structure of carbon in the terracotta matrix. The possibility of suitably decrease electric resistance and increase water retention/leaching of composite A opens the way to a new class of resistive materials that can be simultaneously used as an electrolytic separator and an external electric circuit, allowing a compact microbial fuel cell design. A proof of concept of such MFC design was provided for different tested composites. Although all the anolytes become anaerobic, only the MFCs equipped with the composite A30% were able to produce power, reaching the maximum power peak in correspondence of resistance of about 1 kΩ. The low, but significant, produced power (about 40 mW m-2, cathode area) confirm that the proposed solution is particularly suitable for nutrient recovery and environment pollution bioremediation, where energy harvesting is not requested.